There Was a River - Berger, Bruce (Book collections on Project MUSE., 1994)
Focusing on the interaction of people with the environment, Berger reveals an original vision of the Southwest that encompasses both city and wilderness. In a concluding essay centering on the sale of his mother's estate in Phoenix, he concedes that "our intention to leave the desert alone has resulted, unwittingly, in loss after loss, simply by our being here." Sometimes there are losses - a canyon, a house - but Berger attunes us to the prodigies of change